2021
DOI: 10.1080/02739615.2021.1890077
|View full text |Cite
|
Sign up to set email alerts
|

Psychological outcomes after pediatric hospitalization: the role of trauma type

Abstract: Physical injury and illness are common potentially traumatic events during childhood and adolescence. Many children experience psychosocial difficulties after medical events. The sample consisted of 399 children aged 4 to 15 who had been hospitalized for physical illness or injury. Elevated psychological symptomatology (PTSS, depression, anxiety) was more frequent after multiple (type II) compared to single (type I) medical events, but only a few differences were statistically significant. The strongest risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…PTSS, depression, and anxiety are the most common symptoms experienced by hospitalized children. Therefore, pediatric nurses need to know the signs of stress in children and parents and should have the ability to overcome the impact of hospitalization on children (Meentken et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PTSS, depression, and anxiety are the most common symptoms experienced by hospitalized children. Therefore, pediatric nurses need to know the signs of stress in children and parents and should have the ability to overcome the impact of hospitalization on children (Meentken et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety is a problem generally experienced by hospitalized children. About 25-38% of children experience long-and short-term hospitalization, and 7-40% of these children have unpleasant experiences and symptoms of anxiety (Meentken et al, 2021;Sen, 2020). In Indonesia, several studies have demonstrated that 50-80% of hospitalized children show an anxiety reaction (Juwita, 2019;Wilujeng, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,15,[18][19][20][21][22][23] Life events such as parental separation or divorce, death of a family member or another close person, 19,23 family environment events such as frequent parental arguments, the arrival of a new sibling, or a stepparent moving in 19 are strongly associated with depressive symptoms. The risk of depressive symptoms is also increased by the child's serious illness 9,[23][24][25] or the illness of a parent or relative, or by the loss of a parent or close relative. 11,13,19,23 Also, children whose parents have a history of depression report more depressive symptoms after stressful life events than children whose parents have no depressive history.…”
mentioning
confidence: 99%